Synthesis and characterization of lanthanum silicate oxyapatites co-doped with A (A = Ba, Sr, and Ca) and Fe for solid oxide fuel cells - Cao, X.; Jiang, San Ping (R S C Publications, 2014)
The co-doped lanthanum silicate oxyapatites, La9.5A0.5Si5.5Fe0.5O26.5 (A = Ba, Sr, and Ca), are synthesized by the high-temperature solid state reaction process. The phase formation and structure properties of undoped lanthanum silicate oxyapatite (La9.67Si6O26.5, LSO), Fe-doped lanthanum silicate oxyapatite (La10Si5FeO26.5, LSFO) and co-doped lanthanum silicate oxyapatites (La9.5A0.5Si5.5Fe0.5O26.5, A = Ba, Sr, and Ca) are characterized by X-ray diffraction (XRD) and scanning electron spectroscopy (SEM). The effect of co-doping of A (A = Ba, Sr, Ca) and Fe on the microstructure, sinterability and oxide ion conductivity of lanthanum silicate oxyapatites is investigated in detail. The results show that, as compared to LSO and LSFO oxyapatites, co-doping of A (A = Ba, Sr, and Ca) and Fe significantly benefits the sintering and densification process, and enhances the oxide ion conductivity. For co-doped oxyapatites, the oxide ion conductivities are related to the dopant size, the best properties are obtained for the oxyapatite co-doped with Ca and Fe. The co-doped La9.5Ca0.5Si5.5Fe0.5O26.5 (LCSFO) oxyapatite is a good electrolyte for SOFCs, with an oxide ion conductivity of 1.39 × 10−2 S cm−1 at 800 °C and a low activation energy of 90.71 kJ mol−1. The bulk density and oxide ion conductivities of co-doped oxyapatite ceramics increase significantly with the increase of the sintering temperature. The grain bulk and grain boundary resistances of La9.5Ba0.5Si5.5Fe0.5O26.5 (LBSFO), La9.5Sr0.5Si5.5Fe0.5O26.5 (LSSFO) and LCSFO oxyapatite ceramics are significantly smaller than those of LSO and LSFO oxyapatite ceramics sintered under the identical conditions.